Upaya meningkatkan sikap kerjasama kelompok menggunakan model problem based learning (PBL) berbasis eksperimen materi bencana alam kelas V SDN Pahonjean 03: Cooperation, pbl - Tiwi Aldila, Nuri Evelyn; Nugroho, Agung (IKIP Siliwangi, 2025)
This study attempts to improve the attitude of group cooperation of students using the Problem Based Learning (PBL) model based on experiments on natural disaster material. The research was conducted at SD N Pahonjean 03. The object of this research was 26 fifth grade students, each consisting of 11 male students and 15 female students. Data collection in this study used tests and non-tests. The results of the study using the PBL model showed an increase in student cooperation through experimental-based learning activities. The results of the student cooperation questionnaire in cycle II showed an increase from 40% at the second meeting of cycle I to 83% at the fourth meeting of cycle II. This is included in the Very Good category, and exceeds the completion limit of the success indicator of 75%. Keywords: cooperation, PBL.